Dual Axis Writing Controlled Robot for Physically Handicapped People - R.Vani, Vinod Kumar Udutha, Sai Krishna Prasad Kammili, Pavan Sai Kolagani, Lokesh.D, G.SaranyaDevi (International Journal of Advanced Science and Technology, 2020)
Today more people prefer robots to do their work, because robots have more versatile, accurate, reliable and also reduce human efforts. Robots are programmable with similar function of a human arm. It is very challenging for helping the physically challenged people to progress in education field. In this project, we will develop a robot which will help the physically handicapped person to write through their speech. The speech recognition mechanism is used to program with system and makes the user to write what he speaks. A robot is programmed to write down the sentence which a patient or individual pronounces by the microphone. To perform writing operations, the robot is fitted with a pen and it is also used to draw small diagrams. It will be a low cost device. It can be programmed so that the people who are physically challenged can write and can be extended for users to write translate speech for medical applications.